Utilization of CO2 Gas Emission Into Economically Valuable Products In the Form of Carbonate and Alcohol: Article Review - Nuryoto Nuryoto; Heri Heriyanto; Rafiif Nur Tahta Bagaskara (Jurnal Rekayasa Kimia & Lingkungan, 2024)
Climate change can trigger increases in extreme temperature, ice melt, rising sea levels, and changes in precipitation patterns. The contribution of carbon dioxide (CO2) for that causes climate change has a large contribution. Quick and precise steps to reduce CO2 emissions must be taken to avoid further negative impacts, one of which is converting CO2 gas into an economically valuable product. This study is a literature review focused on the utilization of CO2 gas to produce products in the form of sodium carbonate and methanol. The hope was that this study would provide initial information to understand the condition of the chemical reaction process that can produce maximum, effective, and efficient sodium carbonate and methanol products. The purpose of this research was to conduct an analysis related to the variable that affected the chemical reaction in the synthesis of sodium carbonate and methanol using CO2 gas as the raw material, referring to previous research. The study results show that the pH parameter could be used as preliminary information to predict that the absorption process of SOx, NOx and CO2 had occurred in the solvent and chemical reactions. In another study which methanon synthesis, the highest CO2 conversion was achieved using a Cu- ZnOMOF/Al2O3 catalyst, which was 9.1% with selectivity of 86.9%.